Cover Picture: Construction, Enzyme Response, and Substrate Capacity of a Hyaluronan–Cyclodextrin Supramolecular Assembly (Chem. Asian J. 4/2016). Issue 4 (5th February 2016) - Hu, Ping; Chen, Yong; Li, Jing‐Jing; Liu, Yu
Abstract : A supramolecular assembly was constructed with cationic cyclodextrin (EICD) and native hyaluronan (HA). This assembly, composed of spherical solid nanoparticles with negative charges, showed dual enzyme responses (hyaluronidase and esterase). Therein, HA supported hyaluronidase (HAase) recognition sites and the carboxylic ester groups on EICD supported artificial carboxylic esterase recognition sites. Moreover, both cationic (thioflavin T) and anionic (2‐(4‐toluidino)‐6‐naphthalenesulfonic acid) model drugs could bind to the HA/EICD assembly with different binding models. More information can be found in the Full Paper by Yu Liu et al. on page 505 in Issue 4, 2016 (DOI: 10.1002/asia.201501029 ).